INCREASING OIL RECOVERY THROUGH LOW-TENSION POLYMER FLOODING - Sugihardjo Sugihardjo (Testing Center for Oil and Gas LEMIGAS, 1999)
After completing a waterflood activity, the need of enhancing oil recovery (EOR) is essential. The selection of appropriate EOR methods that will be applied to particular field, as an effort to increase oil recovery, mainly depens on the reservoir characteristics and fluid behaviors.